Evaluation of the record keeping system of public health inspectors and the use of the information reported by them at the MOH level, in a selected province of Sri Lanka. - Peiris, S.L (My University, 2005)
This descriptive cross sectional study was undertaken with the objective to evaluate the record keeping system of Public Health Inspectors PHII and the use of information reported by them at the MOH (Medical Officer of Health) level in the North Central Province of Sri Lank A self-administered questionnaire. six checklist: and a focus .group discussion were used as data collection instruments. The knowledge and attitudes of' PHII towards their record keeping system was good and there is a significant association between supervision and quality. of the data provided by them. The pocket Note Book, Monthly Report, Infectious Disease Register, Food Analysis Register, Register and Quarterly School health Return were the most important documents in carrying out their duties. The Sanitation Register, License and Trade Register, Latrine Construction Register, Temporary Building Application Register and the Building Application Register were selected as the most difficult registers to be maintained and the least important documents. There were no proper in-service training conducted in record keeping requirements after the basic training to update the knowledge of PH11. Poor coordination between MOH level and higher levels (district and the central level) regarding review of performance of PH11 is one of the major problems at present. There is a need for a revision of existing record keeping system PH11. The role and responsibilities 0f PH1l also should be revised to get their services 10 address new health problems in the community . He should be empowered to and build his capacity to conduct occupational health screening and injury prevention programmes in the community.